Peran Orang Tua Mendidik Karakter Anak dalam Islam - Heru Mahmudin; Abdul Muhid (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2020)
This study discusses the role of parents in character education for young women according to Islam. This research library research. The main and first character education for children is the family environment. Education in the family is very important and is the main pillar of character building for a child. The family as the smallest social unit is the most important educational environment and is responsible for educating their children. The education provided by parents should provide a basis for children's education regarding the socialization process and their life in society. Good parenting styles will have a good impact on children's development as well as should. The success of character building in children is influenced by the role of parents in educating children. Parents play an important role in forming an intimate and long-lasting interaction system characterized by personal loyalty, love, and affectionate relationships